Quantum-dot assisted spectroscopy of degeneracy-lifted Landau levels in graphene - Itai Keren (Nature Portfolio, 2020)
Here, the authors develop a spectroscopic technique whereby individual defects in an ultrathin hBN dielectric, placed in proximity to graphene, act as quantum dots. Dot-assisted tunneling is highly sensitive to the nearby graphene excitation spectrum, and allows probing of energy splitting in the excited Landau levels.